Pembangunan Manusia Berkelanjutan Melalui Peningkatan Kemampuan Komunikasi Mahasiswa - Kurniawati; Nuri Herachwati; Tri Siwi Agustina (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose In 2022, Indonesia's Human Development Index (HDI) increased by 0.86 percent when compared to 2020, at which time all countries in the world were depressed by the Covid-19 pandemic. Efforts to increase HDI can be done by continuing improve the ability of the younger generation as agents of change who are believed to be the spearhead of the success of human development. The Postgraduate Study Program of UNAIR participates in improving the communication skills of the young generation through community service activities entitled public speaking training for students. This activity aims to improve students' ability to communicate. Design/methodology/approach – This activity was carried out using the Participatory Action Research (PAR) method by building closeness and active involvement of participants. Findings – The results of this training showed an increase in students' communication skills. Students become more aware of the meaning of communication, and they are also more courageous and not nervous to communicate face-to-face with others after attending public speaking training. Originality/value – This activity can have a significant impact for students directly, and the communication skills and self-confidence of students increase. Students will be able to manage their nervousness, especially when they have to face the audience, besides that students will be able to convey their opinions effectively both in internal and external campus forums. Another implication of this activity is the increase in HDI.